SCIDOT-47. EFFECT OF ulRFE COGNATES EMULATING BIOACTIVE SUBSTANCES ON ANIMAL BEHAVIOR. (11th November 2019) - Figueroa, Xavier; Butters, Mike; Donnell, Scott
Abstract: BACKGROUND: The EMulate Therapeutics Voyager system produces a magnetic field obtained from the magnetic fluctuations produced by molecules in solution. These recordings, ultra-low radio frequency energy ( ul RFE ® ) cognates, are intended to emulate the effects of the molecule. METHODS: Mice were treated with cognates for up to 120 min on the first day, then 24 h/day for the next 15 days. RESULTS: All ul RFE cognates were well tolerated. Body weights remained stable. Animals exposed to signals derived from melatonin, THC (tetrahydrocannabinol), scotch, and ethanol showed signs of mild hypo-activity, while cognates derived from CBD (cannabidiol), Everclear, nicotine, and white wine showed mild signs of somnolence. Caffeine exposure initially caused mild hyperactivity, which returned to normal after the 120 minutes. The espresso cognate induced signs of mild hyperactivity during the initial 20-minute exposure. After 40 minutes, mild head convulsions and normal activity levels were noted. After 120 minutes, signs of hypoactivity were seen. Animals exposed to caffeine ul RFE showed signs of mild hyperactivity for the duration of the 15-day exposure, and animals exposed to nicotine, melatonin, THC, CBD, Everclear, scotch, and white wine cognates experienced mild hypo-activity. Animals exposed to espresso or 100% ethanol ul RFE remained normal during the 15-day exposure. CONCLUSIONS: Mice displayed altered behavior when exposed to the magnetic field produced by the cognates, which, at least in part, were consistent with some effects that would be anticipated for the molecules used to create the cognates. The ul RFE technology offers potential to emulate the effects of bioactive substances across the blood:brain barrier.